IMPLEMENTASI MANAJEMEN STRATEGIK PENDIDIKAN KARAKTER DI SMPN 2 MATARAM - Irawan, M. Ary; Faqih, Muhammad (Jurnal Paedagogy, 2020)
This study aims to describe the strategic planning, implementation, and control of the character education program at SMPN 2 Mataram. This research uses qualitative research. Methods of qualitative data analysis through three activities, namely (1) data reduction (2) data presentation, and (3) drawing conclusions and verification. The results of this study are formulated in 3 conclusions, namely First, strategic planning includes: (1) Formulation of the Vision and Mission of Schools Based on the Value of Cultural Education and National Character, and (2) Character Education is planned systematically. Second, strategic implementation includes: (1) Utilization of the School Environment, (2) Program for Habitual Activities in Schools, (3) Collaboration with other parties, (4) Exemplary in the School Environment, (5) Developing school culture, (6) Providing learning service programs, (7) Strengthening school discipline, and (8) Strengthening character education through systematic and continuous co-curricular and extracurricular activities. Third, strategic control of character education includes: (1) Control is carried out by each teacher through observation, provision of self-assessment and peer assessment instruments, (2) Analyzing the facts of the findings, and (3) Carrying out follow-up and continuous improvement.